2013
DOI: 10.1007/s10120-013-0310-6
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided intensity-modulated radiotherapy for patients with locally advanced gastric cancer: a clinical feasibility study

Abstract: Background The aim of this study was to determine the medical and technical feasibility of intensity-modulated radiotherapy (IMRT) in high-risk nonmetastatic gastric cancer stage II and III after primary gastrectomy and D2 lymphadenectomy. Methods and materials A prospective nonrandomized phase II trial was performed on 25 consecutive patients with gastric cancer with high risk (T3-4, N1-3, G2-3, R0-1). The dose delivered was 45 Gy (1.80 Gy per fraction) in IMRT technique. Concurrent 5-fluorouracil-based chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In our study, we used 5/7-field IMRT, with an incidence of grade 3 hematological toxicities during treatment of 23.5%; grade 3 gastrointestinal reactions of 13.7%; grade 1-2 liver and kidney function impairment of 9.8%; and grade 3 liver and kidney function impairment of 0%; these findings were similar to the results reported by Badakhshi et al (24). In addition, we observed that grade 3 hematological toxicities and gastrointestinal reactions mostly occurred due to the cumulative effect of subsequent adjuvant chemotherapy, and the toxic effects were usually grade 1-2 during concurrent CRT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, we used 5/7-field IMRT, with an incidence of grade 3 hematological toxicities during treatment of 23.5%; grade 3 gastrointestinal reactions of 13.7%; grade 1-2 liver and kidney function impairment of 9.8%; and grade 3 liver and kidney function impairment of 0%; these findings were similar to the results reported by Badakhshi et al (24). In addition, we observed that grade 3 hematological toxicities and gastrointestinal reactions mostly occurred due to the cumulative effect of subsequent adjuvant chemotherapy, and the toxic effects were usually grade 1-2 during concurrent CRT.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, IMRT also improved the postoperative gastric cancer treatment. Badakhshi et al (24) investigated 25 cases of patients who received concurrent CRT with IMRT after gastric cancer surgery, and observed that the incidences of grade 3 nausea and diarrhea during treatment were 4 and 8%, respectively, and the incidences of grade 3 decrease in hemoglobin level, leukocyte and platelet counts were 12, 25 and 4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT allows physicians to target the tumor while sparing nearby organs at risk, simultaneously reducing toxicity as well as improving coverage of the target volume. Previous studies have exhibited IMRT to be feasible in treating gastric cancer [39, 40], and in fact have also demonstrated a reduction in toxicity with this approach [41]. However, the use of IMRT for a moving target is yet another obstacle.…”
Section: Discussionmentioning
confidence: 99%
“…And VMAT can minimize heart damage, which presages the possible use of VMAT to patients with cardiac comorbidities (Campbell et al 2012). Data from several studies suggest that IMRT can reduce mean heart dose and cardiac adverse events for patients with breast cancer, NSCLC, and gastric carcinoma (Maraldo et al 2013;Badakhshi et al 2014;Sakka et al 2017;Jagsi et al 2018). IMRT impacted by multiple criteria optimization (MCO) can reduce the mean heart dose, with the presupposition of insuring treatment effectively.…”
Section: Preventionmentioning
confidence: 99%